Tutor profile: Dylan M.
What is the diameter of a circle with an area of 64*pi ? Hint: A= pi * r^2
Its important to remember that the radius is half the diameter. By using the above equation and plugging in 64*pi for A. You get 64 * pi = pi * r^2. if you divide by pi it cancels on both sides. This gives 64 = r^2. The next step is to get r isolated. This is done by taking the square root of both sides. This gives 8 = r. Now the original question was asking for the diameter not the radius. Which means that d = 16, since its double the radius.
12x – 17 = 151 solve for x.
The goal of this problem is to isolate the variable x. This can be done by moving all the numbers that aren't directly attached to the variable to the other side first. I.E. bring 17 to the other side by adding. This gives 12x = 151 + 17; 12x = 168; now since the 12 and x are being multiplied you must do the opposite which is division, in this case. 12x/12 = 168/12 ; the 12's on the left side cancel one another, now x = 14. This can be checked by plugging the value you find back into the original equation. Its good practice to do this in the beginning so that you become more comfortable with it. I.E. 12*(14) - 17 = 151 ; 168 - 17 = 151 ; 151 = 151. this shows that 14 is correct.
Solve the system of equations. y = –3x + 4 x + 4y = –6
You can solve this by using the substitution method or the elimination method. substitution way would be to solve for either x or y in one of the equations, than substitute that into the other equation. in this example its already solved "y" for us. I.E. " y = -3x+4" by plugging into the other equation it becomes " x + 4(-3x+4) = -6" At this point you may realize that there is now only one term in the equation. Now you have to distribute the 4 to each value in the parenthesis. I.E. 4*-3x = -12x, 4*4=16 ; which gives x - 12x +16 = -6, in this step you may combine like terms. -11x = -22, which gives x=2. once you know one of the variables you may plug it into either of the original equations to find the other variable. In this case i'll plug it into the second equation. x + 4y = -6; (2) + 4y = -6; 4y = -8; y = -2
needs and Dylan will reply soon.